On the analyticity of the Fourier original and Fourier transform inside alternate angles - Cherskii, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We prove that a Fourier image is an analytic function inside two alternate angles if the Fourier preimage possesses the same property.